A randomised clinical in situ study to evaluate the effects of novel low abrasivity anti-sensitivity dentifrices on dentine wear. (February 2017) - Seong, J.; Hall, C.; Young, S.; Parkinson, C.; Macdonald, E.; Jones, S. Bodfel; West, N.X.
Abstract: Objectives: To compare the abrasive wear on human dentine in an in situ model associated with use of an experimental low abrasivity anti-sensitivity dentifrice containing 1% alumina and 5% sodium tripolyphosphate (STP) with an experimental ultra-low abrasivity non-alumina 5% STP dentifrice, a higher abrasivity daily-use whitening dentifrice, and water as controls. Methods: This was a single-centre, single-blind, randomised, split-mouth, four-treatment, two-period, crossover in situ study in 29 healthy subjects. Subjects wore bilateral lower buccal appliances, each fitted with four dentine specimens. Study treatments were applied ex vivo (three times daily). Dentine loss was measured by non-contact profilometry after 5, 10 and 15 days' treatment. Results: All 29 subjects were included in the efficacy analysis. Significantly less dentine loss was associated with brushing with the low and ultra-low abrasivity dentifrices than with the higher abrasivity dentifrice at all timepoints (p < 0.01). Brushing with ultra-low abrasivity dentifrice or water resulted in statistically significantly less dentine loss compared with brushing with the low abrasivity dentifrice at all timepoints (p < 0.05). Dentine loss after brushing with ultra-low abrasivity dentifrice was not significantly different from brushing with water. Conclusions: The degree of dentine loss observed in this in situ model reflected the abrasivity of the study dentifrices. Brushing with low or ultra-low abrasivity STP-containing anti-sensitivity dentifrices resulted in significantly less dentine loss (equating to dentine wear) than with a higher abrasivity daily-use whitening dentifrice.